Refining genotype–phenotype correlation in Alström syndrome through study of primary human fibroblasts. Issue 4 (15th May 2017) - Chen, Jian‐Hua; Geberhiwot, Tarekegn; Barrett, Timothy G.; Paisey, Richard; Semple, Robert K.
Abstract: Background: Alström syndrome (AS), featuring retinal dystrophy, neuronal deafness, cardiomyopathy, metabolic syndrome, and diffuse fibrosis, is caused by biallelic mutations in the centrosomal protein ALMS1. Genotype–phenotype correlation has been suggested without assessment of ALMS1 expression. Methods: ALMS1 expression (real‐time PCR and immunocytochemistry) and cilia formation (immunocytochemistry) were assessed in fibroblasts from deeply phenotyped volunteers diagnosed with AS recruited from a dedicated AS Service. Exome sequencing was used in two participants without convincing biallelic ALMS1 mutations, and BBS2 (Bardet–Biedl syndrome 2) protein expression was assessed in one patient with biallelic BBS2 mutations. Hedgehog‐induced GLI1 expression and PDGFA signaling was assessed using quantitative real‐time PCR, immunoblotting, or immunostaining of fixed cells after stimulation. Results: In 16 of the patient cell lines examined, ALMS1 protein was undetectable (14 with biallelic loss‐of‐function (LoF) mutations), and in two, ALMS1 staining was equivocal (one with biallelic LoF mutations). In five lines, ALMS1 expression was normal using at least one fixation method (one with biallelic LoF mutations). These differences were not accounted for by major differences in ALMS1 mRNA expression. Exome sequencing of two participants with normal ALMS1 expression identified biallelic LoF BBS2 mutations in one. No second, known ciliopathy mutation was found in the other patient, who had one LoF ALMS1 mutation. Phenotypes were milder or atypical in participants with preserved ALMS1 immunostaining, even when two with likely alternative genetic diagnoses were excluded. All cells studied developed normal cilia, ALMS1 and BBS2 mutant cells showed normal Hedgehog‐induced upregulation of GLI1 expression, and PDGFA signaling was normal in ALMS1‐deficient cells. Conclusion: Milder or atypical presentations of AS should prompt genetic evaluation for alternative, clinically overlapping ciliopathies. A subgroup of patients with bona fide ALMS1 defects have milder phenotypes due to residual ALMS1 expression, which may be more important than mutation site. Abstract : Alström Syndrome is a severe multiorgan disorder caused by recessive mutations in the centrosomal protein ALMS1. It overlaps clinically with other ciliopathies, and milder or atypical cases may be explained either by an alternative genetic diagnosis, or by residual ALMS1 protein expression despite biallelic loss‐of‐function mutations.